Sensorial, chemical and microbiological quality of anchovy cake - Inanli, Ayse Gurel; Karaton, Nermin; Coban, Ozlem Emir (Academic Journals, 2011)
In this study, fish cake prepared using raw anchovy (Engraulis encrasicolus) and its products were stored in a locked bag at a cold temperature of 4 +/- 1 degrees C. Moisture, ash, fat, protein, salt, pH, TVB-N, number of TBA, TMA-N and histamine values, number of total aerobic microorganisms (at 5 and 30 degrees C temperature of incubation) and yeast-mold were determined in the raw material during the production period. Sensorial, chemical (pH, TVB-N, number of TBA, and TMA-N values) and microbiological changes during cold storage period of the products were carried out every 3 days and with three replications. In this study, the prepared product was appreciated by the panelists that participated in the sensorial analyses. In addition, as the values obtained from sensorial, chemical and microbiological values were evaluated, the shelf-life of the anchovy cake during cold storage (4 +/- 1 degrees C) was found to be 6 days.
Keywords: Anchovy cake; shelf-life; chemical; sensorial; microbiological; Engraulis encrasicolus